2017
DOI: 10.1101/186973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ceasing the use of the highest priority critically important antimicrobials does not adversely affect production, health or welfare parameters in dairy cows

Abstract: Due to scientific, public and political concern regarding antimicrobial resistance (AMR), several EU countries have already taken steps to reduce antimicrobial (AM) usage in production animal medicine, particularly that of the highest priority critically important AMs (HP-CIAs). While veterinarians are aware of issues surrounding AMR, barriers to change such as concerns of reduced animal health, welfare or production may inhibit AM prescribing changes.Farmers from seven dairy farms in South West England engage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Dutch farmers and veterinarians were unsure whether a cow would recover without antimicrobials (Scherpenzeel et al 2016;Scherpenzeel et al 2018) and many Dutch veterinarians reported it is their duty to treat diseased animals for reasons of animal welfare, regardless of the issue of AMR (Speksnijder et al 2015). Despite these findings, research in the UK dairy sector found that ceasing the use of the highest priority critically important antimicrobials can occur while maintaining herd health and farm productivity (Turner et al, 2018). These findings highlight the responsibility to animal welfare felt by farmers and veterinarians; thus they feel that antimicrobials are essential to preserve animal welfare and productivity.…”
Section: Theme 3: Barriers and Facilitators To Reduced Antimicrobial ...mentioning
confidence: 99%
“…Dutch farmers and veterinarians were unsure whether a cow would recover without antimicrobials (Scherpenzeel et al 2016;Scherpenzeel et al 2018) and many Dutch veterinarians reported it is their duty to treat diseased animals for reasons of animal welfare, regardless of the issue of AMR (Speksnijder et al 2015). Despite these findings, research in the UK dairy sector found that ceasing the use of the highest priority critically important antimicrobials can occur while maintaining herd health and farm productivity (Turner et al, 2018). These findings highlight the responsibility to animal welfare felt by farmers and veterinarians; thus they feel that antimicrobials are essential to preserve animal welfare and productivity.…”
Section: Theme 3: Barriers and Facilitators To Reduced Antimicrobial ...mentioning
confidence: 99%
“…Recent European studies have shown that antimicrobial usage can be reduced concurrent with improved management strategies, with a particular focus on biosecurity, without adversely affecting farm productivity [57,58] and profitability [59]. Similarly, the withdrawal of HP CIAs did not adversely affect production, health or welfare parameters on UK dairy farms [60]. In many countries, there is an emphasis on communication of best practice to farmers, to improve animal health and thereby reduce the need for antimicrobials.…”
Section: Additional Measuresmentioning
confidence: 99%
“…As reviewed here, this may require further improvements in convenience characteristics and scientific criteria of POC tests and changes in knowledge, attitudes and behaviours among veterinarians and dairy farmers. Behaviour change should also include refinement, whereby we should abstain from the use of HP-CIA in dairy cattle (Turner et al, 2018). Professionals in the dairy industry, processors, retailers, pharmaceutical companies and regulators all have a role to play in reduction and refinement as they buy milk, or produce, approve and market antimicrobial products.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…The World Health Organization (WHO) has identified Highest Priority Critically Important Antimicrobials (HP-CIA) for human medicine (WHO, 2019), and suggested that HP-CIA 'should not be used for treatment of foodproducing animals with a clinically diagnosed infectious disease' (WHO, 2017). Quinolones, macrolides and ketolides, polymixins and 3 rd and 4 th generation cephalosporins are all HP-CIA used for mastitis treatment and we can do better in this area (Turner et al, 2018;Doehring and Sundrum, 2019).…”
mentioning
confidence: 99%